PENDIDIKAN KARAKTER DALAM TRADISI KEAGAMAAN MASYARAKAT MUSLIM PAPUA BARAT - Akramun Nisa (Pascasarjana IAIN Sorong, 2019)
This research tries to understand the meaning of character education on the religious tradition of West Papua Muslim community. To process of data collection, the researcher using an interviews, observation and documentation. The results show that from the eight religious traditions analyzed there are ten values of character education. Of the ten values of character education is dominated by religious values and appreciation value especially in the tradition of safar bath, drum sahur, night warning lailatu qadr, implementation of aqiqah and qurban, maulid derivative and maulid fakalah, tombormark and tradition of picking preacher. The learning of character education based on local wisdom is in fact an alternative consideration in teaching and inculcating the values of wisdom in the minds, paradigms, and beliefs of learners by emphasizing the hearts and minds in shaping the characters.